HEALTH EDUCATION ABOUT NEONATAL CARE TO INCREASE NEONATES HEALTH STATUS - Chori Elsera (UNEJ e-Proceeding, 2017)
Background: Infants and children health care is vital at preparing a healthy, smart and qualified generation and reducing infants and children mortality. In the last 5 years, Neonatal Mortality Rate (NMR) remains at 19/1000 births. Apropriate neonatal care can prevent infant’s death and also prevent residual symptoms due to complications or health problems previously. This study purpose to identify effect knowledge to neonates health status in the intervention and control group. Methods: This study was conducted experimentally in the intervention group with control group comparison. The Purpose of this study to describe the knowledge of mothers about neonatal care with neonatal health status. The sample was taken using purposive sampling with 30 respondents in the intervention group and 30 respondents in the control group. Results: There is a significant effect of health education toward mother’s knowledge level about neonatal care (pV = 0.000 ; 0,05). There is no influence between mother's knowledge about neonatal care toward infant health status with p-value = 0,508 (p > 0,005). Conclusion: Infant health status is not influenced by mothers’ knowledge level about neonatal care. Keywords: Neonates, Morbidity, Neonatal Care